Pengaruh Desain Situs Web, Harga, Kepercayaan, Keamanan terhadap Pembelian Produk Fashion melalui Toko Online - Hakim, Cahya Nur; Afsaliani, Dalfa (Applied Business and Administration Journal, 2023)
The industrial era 5.0 created higher internet usage, which encouraged consumers and producers to use internet media to shop online, especially regarding fashion products. To advance the marketing company has a strategy by studying prices, trust, security and even online sales. The purpose of this study is to determine the effect of website design on price, trust, security, and converting potential customers. Sample samples taken were 100 samples randomly selected starting from lecturers and students. The results of this study indicate that there is a good influence on price, security, but there is no effect on website design, trust by shopping online.